High-Q litz wire NQR sensor for medical applications - R. R. Khusnutdinov; G. V. Mozzhukhin; N. R. Khusnutdinova; B. M. Salakhutdinov (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE. The design and development of radio frequency (RF) coil sensors is an important engineering and, at the same time, fundamental task for those radio spectroscopic instruments that require an increase in sensitivity, measured as a signal-to-noise ratio (SNR). Radio spectroscopy of nuclear quadrupole resonance (NQR), especially in nitrogen compounds, in which the resonant frequency is very low and ranges from a few megahertz or lower to hundreds of kilohertz, requires the use of special solutions to increase the sensitivity. PURPOSE. Theoretical substantiation and search for a technical solution that allows achieving high sensitivity on standard equipment through the use of a high-quality sensor. METHODS. Methods for optimizing the design of sensors for NQR/NMR spectrometers are considered. The design of the sensor for the NQR spectrometer, which contains an inductance coil wound with a Litz wire, has been calculated and designed. RESULTS. A high-quality coil for the spectrometer sensor was made, which gives an increase in the quality factor by about 1.5 times. The use of a spectrometer with this coil made it possible to confidently record weak noisy signals of paracetamol at a low duty cycle. The sensitivity of the sensor made it possible to distinguish preparations from different manufacturers by their spectral characteristics. CONCLUSIONS. A solenoid sensor has been developed, modeled and manufactured, which has a high quality factor and allows recording quadrupole resonance signals of drugs (paracetamol) by a non-destructive method directly through the package. The possibility of using such a sensor for quality control of medicines, detection of falsified and counterfeit medicines is shown.